Rancang Bangun Pemilah Sampah Organik dan Anorganik Berbasis Arduino - Dimas Smeichel Maliseono; Muhammad Rizqi Warsita; Rivan Herdyansyah; Naufal Rifqi Azfar; Susilawati, M.Si (Peneliti.net, 2026)
The problem of waste accumulation in Indonesia is often caused by a lack of awareness and inadequate facilities for waste separation at the source. Manual sorting is considered inefficient and poses health risks. The aim of this study is to develop and build a prototype for an automated waste sorting system capable of separating organic and inorganic waste. The research follows an experimental approach using an Arduino Uno R3 as the main controller. The system integrates an HC-SR04 ultrasonic sensor for object detection, an inductive proximity sensor for metal detection, and a TCS3200 color sensor to identify organic waste based on its dominant color (green). Additionally, a DHT22 sensor is used to monitor the ambient temperature inside the waste container. Test results show that the device detects metal waste with 100% accuracy using the inductive sensor and separates organic waste (leaves) from non-metallic inorganic waste with an average success rate of 85% using the color sensor under controlled lighting conditions. This system is intended to provide an effective and hygienic solution for waste separation on a household scale.